Subcortical gray matter changes in transgender subjects after long-term cross-sex hormone administration. (December 2016) - Seiger, Rene; Hahn, Andreas; Hummer, Allan; Kranz, Georg S.; Ganger, Sebastian; Woletz, Michael; Kraus, Christoph; Sladky, Ronald; Kautzky, Alexander; Kasper, Siegfried; Windischberger, Christian; Lanzenberger, Rupert
Highlights: Assessing the influence of high-dose cross-sex hormone administration on the brain. Inclusion of transgender participants undergoing hormonal treatment. Subcortical brain changes in areas related to cognition and emotion. Changes in progesterone levels correlate with changes in gray matter structures. Abstract: Sex-steroid hormones are primarily involved in sexual differentiation and development and are thought to underlie processes related to cognition and emotion. However, divergent results have been reported concerning the effects of hormone administration on brain structure including side effects like brain atrophy and dementia. Cross-sex hormone therapy in transgender subjects offers a unique model for studying the effects of sex hormones on the living human brain. In this study, 25 Female-to-Male (FtM) and 14 Male-to-Female (MtF) subjects underwent MRI examinations at baseline and after a period of at least 4-months of continuous cross-sex hormone administration. While MtFs received estradiol and anti-androgens, FtM subjects underwent high-dose testosterone treatment. The longitudinal processing stream of the FreeSurfer software suite was used for the automated assessment and delineation of brain volumes to assess the structural changes over the treatment period of cross-sex hormone administration. Most prominent results were found for MtFs receiving estradiol and anti-androgens in the form of significant decreases in the hippocampal region. Further analysis revealed that these decreases were reflected by increases in the ventricles. Additionally, changes in progesterone levels correlated with changes in gray matter structures in MtF subjects. In line with prior studies, our results indicate hormonal influences on subcortical structures related to memory and emotional processing. Additionally, this study adds valuable knowledge that progesterone may play an important role in this process.